Harvard Business Review's 10 must Reads the essentials - Harvard Business Review (Boston Harvard Business Review Press, 2011)
Change is the one constant in business, and we must adapt or face obsolescence. Yet certain challenges never go away. That's what makes this book "must read." These are the 10 seminal articles by management's most influential experts, on topics of perennial concern to ambitious managers and leaders hungry for inspiration--and ready to run with big ideas to accelerate their own and their companies' success. If you read nothing else - full stop - read: If you read nothing else - full stop - read: Michael Porter on creating competitive advantage and distinguishing your company from rivals John Kotter on leading change through eight critical stages Daniel Goleman on using emotional intelligence to maximize performance Peter Drucker on managing your career by evaluating your own strengths and weaknesses Clay Christensen on orchestrating innovation within established organizations Tom Davenport on using analytics to determine how to keep your customers loyal Robert Kaplan and David Norton on measuring your company's strategy with the Balanced Scorecard Rosabeth Moss Kanter on avoiding common mistakes when pushing innovation forward Ted Levitt on understanding who your customers are and what they really want C. K. Prahalad and Gary Hamel on identifying the unique, integrated systems that support your strategy Michael Porter on creating competitive advantage and distinguishing your company from rivals John Kotter on leading change through eight critical stages Daniel Goleman on using emotional intelligence to maximize performance Peter Drucker on managing your career by evaluating your own strengths and weaknesses Clay Christensen on orchestrating innovation within established organizations Tom Davenport on using analytics to determine how to keep your customers loyal Robert Kaplan and David Norton on measuring your company's strategy with the Balanced Scorecard Rosabeth Moss Kanter on avoiding common mistakes when pushing innovation forward Ted Levitt on understanding who your customers are and what they really want C. K. Prahalad and Gary Hamel on identifying the unique, integrated systems that support your strategy
Includes bibliographical references and index.
Keywords: Management